Cloud Computing and Education- A Technical Review - Ramzan, Shahid; Irfan, Dr.Mohd (IJRDO -Journal of Computer Science Engineering, 2016)
The objective of present paper is reviewed the technical Aspect of CloudComputing on the Education System. The Class room teaching is a changing and Students arebecoming more technology oriented and Therefore in his changing environment, it’simportant that we think about the latest technologies to incorporate in the teaching andlearning process. One of the latest technologies prevailing now days is Cloud Computing. Bysharing IT services in the cloud, educational institution can outsource noncore services andbetter concentrate on offering students, teachers, faculty, and staff the essential tools to helpthem succeed. Nutshell Cloud computing has the potential for improving the efficiency, costand convenience for the universities and educational sectors.